A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells. Issue 23 (1st December 2020) - Wang, Jiaming; Jin, Mei; Jin, Chunshi; Ye, Chao; Zhou, Yi; Wang, Rongshen; Cui, Huanhuan; Zhou, Wei; Li, Gao
Abstract: A new pentacyclic triterpenoid, 3-oxo-urs-11, 13(18)-dien-28-oic acid (1 ), along with twelve known triterpenoids, α -amyrin (2 ), 19 α -hydroxy- α -amyrin (3 ), triptohypol E (4 ), uvaol (5 ), 2 α, 3 α -dihydroxyurs-11-en-13 β, 28-olide (6 ), 3 β -hydroxyurs-11-en-13 β, 28-olide (7 ), ursolic acid (8 ), asiatic acid (9 ), oleanolic acid (10 ), aegiceradienol (11 ), obtusalin (12 ) and betulinic acid (13 ) were isolated from the leaves of Rhododendron dauricum L. Their structures were established from spectroscopic data and comparison with reported values. Among them, compounds 3, 4, 6, 7 and 11 were isolated from the Ericaceae family for the first time. Compounds 2, 5, 9, 12 and 13 were obtained from R. dauricum for the first time. Additionally, compounds 6, 10 and 11 significantly inhibited the levels of NO in LPS-stimulated RAW 264.7 cells at 3 μM. Abstract :